Football Performance Analysis Technology: A Bibliometric Study (Universitas Pendidikan Indonesia, 2024)
Sophisticated technology, such as the Global Positioning System (GPS), has been widely used in football. GPS is used to analyze the performance of football athletes. Few journals have discussed football performance analysis utilizing technology, with less than a hundred articles published each year. This research aimed to explore, trace, and review the development of research and publications on scientific analysis related to technology in football using bibliometric analysis. The study used the Scopus database, using the keywords (